Identification Comparison of Landslide Potential Area with Analytical Hierarchy Process and Logistic Regression Methods in Cisarua District and Surroundings, Bogor Regency, West Java - Pratama, Agun Romdha Sastra; Misbahudin (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
Landslide is one of the geological disasters that often occur in Indonesia, especially in Cisarua District and its surroundings, Bogor Regency, West Java, so mitigation activities need to be carried out, one of which is by making a map of potential areas of landslide in the research area. This study aims to analyze the spatial distribution of potential landslides in Cisarua District, Bogor Regency, using the Analytical Hierarchy Process (AHP) and Logistic Regression (LR) methods, and to determine the more effective method for landslide prediction in the study area. The results showed that the AHP method obtained the distribution of potential areas of landslide in the low category with an area of 39,592 km2 with a percentage of 38.99%, the moderate category with an area of 39,690 km2 with a percentage of 39.09% and the high category with an area of 22,253 km2 with a percentage of 21.92%. In the LR method, the potential for landslide was obtained in the low category with an area of 39,158 km2 with a percentage of 38,15%, the moderate category with an area of 39,485 km2 with a percentage of 38.86%, and the high category with an area of 22,967 km2 with a percentage of 23% and the best method in determining the potential area of landslide was the LR method with an overall accuracy level of 86.41% compared to the Analytical Hierarchy Process (AHP) method with an overall accuracy of 78.64%.